Investigating the thermodynamics properties of water confined in carbon nanotubes using molecular dynamics simulations - Amit Srivastava; Gobind Das; Sufian Abedrabbo; Jamal Hassan; Dirar Homouz (Scientific Reports)
Abstract Confinement is known to significantly influence the properties of water, yet the precise mechanisms, particularly within nanotubes of varying diameters, remain under investigation. This study examines how confinement impacts the structural and thermodynamic behavior of water molecules inside carbon nanotubes (CNTs) with diameters ranging from 0.8 nm to 3.0 nm, across temperatures from 230 K to 420 K. We present findings on entropy, radial density, self-diffusion coefficients, and orientational order parameters derived from molecular dynamics simulations. Our results reveal that in ultra-narrow 0.8 nm CNTs, water molecules forms a single-file arrangement with some offset molecules, leading in two distinct peaks in the density profile, which differs from earlier reports suggesting a single peak for single-file water. In 0.8 nm CNTs, water demonstrates subdiffusive behavior, whereas larger CNTs show Fickian diffusion. Further analysis reveals a shift from non-Arrhenius to Arrhenius thermodynamic behavior along the CNT axis with increasing temperature. Additionally, a freezing transition of water is observed in 1.0 nm CNTs. Entropy analysis suggests that confined water is more stable than bulk water, though this stability is influenced by the degree of confinement. This study provides deeper insights into the structure and dynamics of water under confinement.